PRELIMINARY PHYTOCHEMICAL INVESTIGATION OF WHOLE PLANT OF ALYSICARPUS MONILIFER (L.) DC - K. KARTHIKEYAN,; C.K.DHANAPAL,; G. GOPALAKRISHNAN, (International Journal of Pharma and Bio Sciences, 2015)
To evaluate the phytochemical activity of different extract of aerial parts of Alysicarpus monilifer belonging to the family Fabacea. The aerial parts were collected and extract prepared from petroleum ether, ethyl acetate and methanol by hot continuous percolation method in a Soxhlet apparatus for 24 hrs. The preliminary phytochemical investigation shows presence of alkaloids, proteins & free amino acids, glycosides, phytosterols, saponins,carbohydrates & free reducing sugars, tannins & phenolic compounds and flavonoids. Each active compound shows different activities against different types of diseases like cancer, liver disorders, diabetes, atherosclerosis and inflammatory diseases etc. According to their characteristics, they can be involved in the medicinal plant category.